The effect of organic fertilizer on the growth of cocoa seedlings / Mohammad Afif Osman - Osman, Mohammad Afif (Faculty of Plantation and Agrotechnology, 2015)
A study was conducted in rain shelter at Universiti Teknologi Mara (UiTM) kampus Jasin for three months to investigate the effects of organic fertilizers. The treatments were poultry dung, cow dung, compost EFB, poultry dung + cow dung, poultry dung + compost EFB, cow dung + compost EFB, poultry dung + cow dung + compost EFB and NPK 15:15:15. The fertilizer we applied at 0.25kg per plant in the polybag size 10 inch times 12 inch and arranged into completely randomized design (CRD) replicated five times. The plants watered daily at 0.35 litre and the data were collected once a week. The growth performance on cocoa seedling as demonstrated show the result that poultry dung, cow dung, compost EFB can be used as fertilizer. However, this fertilizer still cannot fulfil the demand of cocoa seedlings. All of the treatments showed positive reaction towards growth. The parameters that have significant different are numbers of leaves and dry weight.